Der beste Tageszeitpunkt für Checkpoint-Inhibitoren (Deutsche Zeitschrift für Onkologie, 2022)
Qian DC, Kleber T, Brammer B et al. Effect of immunotherapy time-of-day infusion on overall survival among patients with advanced melanoma in the USA (MEMOIR): A propensity score-matched analysis of a single-centre, longitudinal study. Lancet Oncol 2021; 22: 1777–1786. doi:10.1016/S1470-2045(21)00546-5